1996
DOI: 10.1074/jbc.271.45.28168
|View full text |Cite
|
Sign up to set email alerts
|

The Location of the Active Site of Blood Coagulation Factor VIIa above the Membrane Surface and Its Reorientation upon Association with Tissue Factor

Abstract: The topography of membrane-bound blood coagulation factor VIIa (fVIIa) was examined by positioning a fluorescein dye in the active site of fVIIa via a tripeptide tether to yield fluorescein-D-phenylalanyl-L-prolyl-Larginyl-fVIIa (Fl-FPR-fVIIa). The location of the activesite probe relative to the membrane surface was determined, both in the presence and absence of tissue factor (TF), using fluorescence energy transfer between the fluorescein dye and octadecylrhodamine (OR) at the phospholipid vesicle surface. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
76
0
2

Year Published

1997
1997
2006
2006

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 73 publications
(89 citation statements)
references
References 44 publications
11
76
0
2
Order By: Relevance
“…Although the position of the active site above the membrane surface has been postulated to be functionally important (12,13,15,16,43), the data reported here constitute the first direct demonstration that modulation of active site location can alter enzyme activity and that the cofactor can be rendered irrelevant by the appropriate repositioning of the active site. Thus, we conclude that protein-dependent modulation of topography (specifically, structure relative to the membrane surface) is an effective means to regulate the activity of membrane-bound enzymes involved in hemostasis and likely in other membranedependent processes.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Although the position of the active site above the membrane surface has been postulated to be functionally important (12,13,15,16,43), the data reported here constitute the first direct demonstration that modulation of active site location can alter enzyme activity and that the cofactor can be rendered irrelevant by the appropriate repositioning of the active site. Thus, we conclude that protein-dependent modulation of topography (specifically, structure relative to the membrane surface) is an effective means to regulate the activity of membrane-bound enzymes involved in hemostasis and likely in other membranedependent processes.…”
Section: Discussionmentioning
confidence: 88%
“…For example, tissue factor was found to alter the location of the active site of membrane-bound factor VIIa relative to the membrane surface (15), and this position was dictated by the cofactor, not by the membrane binding Gla domain of factor VIIa (39). Also, factor Va binding to factor Xa on a membrane surface causes translocation and/or rotation of the active site of the enzyme relative to the membrane surface (13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This conclusion is true for both point-to-point (e.g., refs. 17, 21, 25, and 26) and plane-toplane (18,23,27,28) FRET measurements. Furthermore, because Rh-PE is oriented randomly in the plane of the membrane in the plane-to-plane FRET measurements done here, the uncertainty in R 0 due to orientation effects is further reduced.…”
Section: Dye Orientation ( 2 ) Effects and Uncertainties In Lmentioning
confidence: 99%
“…It has been hypothesized that an important role for membrane-bound cofactors such as TF is to fix the active site of their cognate protease at the optimal position and orientation relative to the membrane surface for attack on the scissile bonds of membrane-bound protein substrates (10,11). Using fluorescence resonance energy transfer (RET) techniques, we previously showed that when fVIIa binds to phospholipid membranes, its active site is located 83 Å above the membrane surface, but this distance shortens to about 75 Å when fVIIa binds to TF (11). This was true even when the fVIIa Gla domain was removed, demonstrating that TF alone is sufficient to dictate the location of the fVIIa active site above the membrane surface (12).…”
mentioning
confidence: 99%